1971
DOI: 10.1037/h0031741
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in vocational development of urban youth.

Abstract: This study investigated the vocational maturity of lower-and middle-class adolescent boys. The Readiness for Vocational Planning Scale was administered to 375 students in Grades 8 through 12. The mean scores show that the lowerclass students were slower in developing vocational maturity. A univariate analysis of covariance indicated a significant difference among the groups and Scheff6 post hoc comparisons found the differences to be in Grades 10, 11, and 12 between lower-class and middle-class students withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Gribbons and Lohnes (1968) reported growth from grades 8 to 10 in various aspects of readiness for vocational planning. Ansell and Hansen (1971) found similar results across grades 8 through 12 in a crosssectional study of lowerand middle-class high school boys.…”
supporting
confidence: 55%
“…Gribbons and Lohnes (1968) reported growth from grades 8 to 10 in various aspects of readiness for vocational planning. Ansell and Hansen (1971) found similar results across grades 8 through 12 in a crosssectional study of lowerand middle-class high school boys.…”
supporting
confidence: 55%
“…Although career maturity differences among the adolescents' three ethnic groups do exist, these differences may be more associated with factors within socioeconomic backgrounds than with ethnic group memberships. This conclusion supports Ansell and Hansen's (1971) research finding of career development differences between Black and Anglo males; yet these investigators concluded that the differences were related more to socioeconomic background than to ethnic group membership (or race). These latter career maturity differences in the present study suggest a trend wherein the adolescents' career choice attitude maturity increased from lower socioeconomic status to middle socioeconomic status.…”
Section: Discussionsupporting
confidence: 80%
“…Unfortunately, research findings on ethnic minority group members' career developments are both confusing and inconsistent (Osipow, 1973). For example, Ansell and Hansen (1971) concluded from their study that variations in readiness for career planning were present, but they appeared to be related more to socioeconomic status than to ethnic group membership (or race) of the students. Comparing inner-city Anglo and Black male students with suburban Anglo students, Maynard and Hansen (1970) found Anglo and Black male differences in career maturity, but these differences were negligible when intelligence was controlled.…”
mentioning
confidence: 99%
“…More specifically, that as a predictor variable, self-concept seems to have a lesser effect on career maturity than the predictor variables of race and sex. Ansell and Hansen (1971) found that race was not an apparent factor in career development. Shappell and Hall (1971) concluded that sex is not a factor in differentiating perceptions of careers.…”
mentioning
confidence: 98%